Reconstructing the concept of school climate. Issue 2 (3rd April 2022) - Konishi, Chiaki; Wong, Tracy K. Y.; Persram, Ryan J.; Vargas-Madriz, Luis Francisco; Liu, Xuedi
ABSTRACT: Background: School climates have broad-ranging implications for students' success and well-being, with research suggesting that a positive school environment plays a crucial role. However, more needs to be understood about school climate from students' points of view. Purpose: This study sought to explore what constitutes school climate from students' perspectives. Method: In this qualitative study, 22 grade 8 to 11 students (ages 13–18) from a secondary school in Canada participated in semi-structured focus group discussions (6 to 8 students per group). The students described their perceptions of school climate from their own perspectives. Later in the session, the students were introduced to ten school climate dimensions identified in a previous study and asked whether they would remove any dimensions or add new ones. Data were transcribed and analysed in depth, using thematic coding. Findings: The analysis yielded fifteen main dimensions, of which seven represented those identified in the previous study. The remaining eight dimensions emphasised the uniqueness of students' experiences and the facets that they value in school climate. These included the availability of school resources, leadership, teacher professionalism, student-teacher relationships, a sense of order, and support. Conclusions: Understanding school climate plays a critical role in efforts to foster a positive school environment for students. Our study highlights the need for multi-reporter methodologies to fully comprehend the complexity of school climate, thereby helping to inform policies and professional development practices that aim to improve school climates.